Mr. Wolf's class : lucky stars - Steinke, Aron Nels (Graphix, an imprint of Scholastic, 2019)
When the students in Mr. Wolf's class learn about personal narratives, Sampson doesn't think anything worth writing about has ever happened to him, until a bicycle accident gives him a new perspective.